The Future of India's Social Safety Nets - Rahman, Andaleeb (Palgrave Studies in Agricultural Economics and Food Policy, 2024)
India has learned what to do and what not to do when it comes to implementing policy to address human suffering. The COVID-19 pandemic unified the international response in similar ways, and the world has a lot to learn about key initiatives in India that have been implemented since India's independence. This open-access book includes key learnings about the conceptualization, design, and impact of social welfare programs in India spanning more than a 75-year period. The Future of India's Social Safety Nets provides a comprehensive analysis of these systems by combining insights from a wealth of interdisciplinary scholarship on social protection, economic development, and social policy. It covers India’s social development in terms of three essential aspects of policy design: focus (intended beneficiaries), form (transfer modalities), and scope (developmental objectives). Highlighting the developmental achievements and shortcomings of the myriad of social welfare schemes, this book proposes a framework to foster human resilience through social protection. This is an open-access book.